The influence of individual executives on corporate financial reporting: A review and outlook from the perspective of upper echelons theory. (15th October 2016) - Plöckinger, Martin; Aschauer, Ewald; Hiebl, Martin R.W.; Rohatschek, Roman
Abstract : In recent years, numerous studies have investigated whether individual executives and their characteristics relate to financial reporting choices. In this article, we review archival, experimental and survey research on the influence of individual executives on corporate financial reporting and use upper echelons theory as our organizing framework. Our review of 60 studies shows that research consistently finds that top management executives exert significant influence on financial reporting decisions, particularly on disclosure quality. Empirical research has developed promising approaches to investigate executives' psychological attributes and character traits. The results of studies examining the influence of demographic characteristics of individual executives are, however, sometimes contradictory and ambiguous. Nevertheless, the overall empirical results we review are supportive of upper echelons predictions. Additional research in this field is needed to clarify the influence of unexamined upper echelon characteristics, important moderator variables, and adverse selection effects. We also suggest that future research more closely investigates the magnitudes of managerial influence and adopts a more holistic perspective on financial reporting outcomes.